Observations of plasma density structures in association with the passage of traveling convection vortices and the occurrence of large plasma jets. - Van Eyken, A.P.; Valladares, C.E.; Alcaydé, D.; Rodriguez, J.V.; Ruohoniemi, J.M. (European Geophysical Society, 1999)
We report important results of the first campaign specially designed to observe the formation and the initial convection of polar cap patches. The principal instrumentation used in the experiments comprised the EISCAT, the Sondrestrom, and the Super DARN network of radars. The experiment was conducted on February 18, 1996 and was complemented with additional sensors such as the Greenland chain of magnetometers and the WIND and IMP-8 satellites. Two different types of events were seen on this day, and in both events the Sondrestrom radar registered the formation and evolution of large-scale density structures. The first event consisted of the passage of traveling convection vortices (TCV). The other event occurred in association with the development of large plasma jets (LPJ) embedded in the sunward convection part of the dusk cell. TCVs were measured, principally, with the magnetometers located in Greenland, but were also confirmed by the line-of-sight velocities from the Sondrestrom and SuperDARN radars. We found that when the magnetic perturbations associated with the TCVs were larger than 100 nT, then a section of the high-latitude plasma density was eroded by a factor of 2. We suggest that the number density reduction was caused by an enhancement in the O+ recombination due to an elevated Ti, which was produced by the much higher frictional heating inside the vortex. The large plasma jets had a considerable (>1000 km) longitudinal extension and were 200-300 km in width. They were seen principally with the Sondrestrom, and SuperDARN radars. Enhanced ion temperature (Ti) was also observed by the Sondrestrom and EISCAT radars. These channels of high Ti were exactly collocated with the LPJs and some of them with regions of eroded plasma number density. We suggest that the LPJs bring less dense plasma from later local times. However, the recent time history of the plasma flow is important to define the depth of the density depletion. Systematic changes in the latitudinal location and in the intensity of the ...